Gamma-mangostin Protects S16Y Schwann Cells Against tert-Butyl Hydroperoxide-induced Apoptotic Cell Death - Charoensuksai, Purin; Arunprasert, Kwanputtha; Saenkham, Audchara; Opanasopit, Praneet; Suksamrarn, Sunit; Wongprayoon, Pawaris (Current Pharmaceutical Design, 2023)
Background: Peripheral neuropathy is a common complication that affects individuals with diabetes. Its development involves an excessive presence of oxidative stress, which leads to cellular damage in various tissues. Schwann cells, which are vital for peripheral nerve conduction, are particularly susceptible to oxidative damage, resulting in cell death.Materials and Methods: Gamma-mangostin (γ-mangostin), a xanthone derived from Garcinia mangostana, possesses cytoprotective properties in various pathological conditions. In this study, we employed S16Y cells as a representative Schwann cell model to investigate the protective effects of γ-mangostin against the toxicity induced by tert-Butyl hydroperoxide (tBHP). Different concentrations of γ-mangostin and tBHP were used to determine non-toxic doses of γ-mangostin and toxic doses of tBHP for subsequent experiments. MTT cell viability assays, cell flow cytometry, and western blot analysis were used for evaluating the protective effects of γ-mangostin.Results: The results indicated that tBHP (50 μM) significantly reduced S16Y cell viability and induced apoptotic cell death by upregulating cleaved caspase-3 and cleaved PARP protein levels and reducing the Bcl- XL/Bax ratio. Notably, pretreatment with γ-mangostin (2.5 μM) significantly mitigated the decrease in cell viability caused by tBHP treatment. Furthermore, γ-mangostin effectively reduced cellular apoptosis induced by tBHP. Lastly, γ-mangostin significantly reverted tBHP-mediated caspase-3 and PARP cleavage and increased the Bcl-XL/Bax ratio.Conclusion: Collectively, these findings highlight the ability of γ-mangostin to protect Schwann cells from apoptotic cell death induced by oxidative stress.
Keywords: Schwann cell